IMPLEMENTASI LITERASI DAN NUMERASI PADA PELAKSANAAN KAMPUS MENGAJAR ANGKATAN 6 DI SD NEGERI 03 SEPAUK KABUPATEN SINTANG - Kurniati, Agusta; Oktaviani, Ursula Dwi; Warkintin, Warkintin (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The government has been started the School Literacy Movement (GLS) program since 2015, which is regulated in Minister of Education and Culture Regulation No. 23 of 2015 concerning the growth of Character. Literacy and numeracy are fundamental competencies which have an important role in determining the quality of a nation. Kampus Mengajar is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs, has come to provide a solution. The activities carried out in the Kampus Mengajar program are assisting with teaching, assisting with technology adaptation, and assisting school administration. Kampus Mengajar students focus on improving the quality of learning and numeracy and literacy skills on elementary school (SD), junior high school (SMP) and vocational high school (SMK) students. One of them is at SD Negeri 03 Sepauk, Sintang Regency. This activity provides experience results that students may not necessarily get through lectures. Implementation of Kampus Mengajar activities can provide knowledge for students to become individuals who have high loyalty and dedication to the country through education, students can also gain insight and experience outside of college.